Analisis Konsumsi Energi Listrik Pada Sistem Pengkondisian Udara Berdasarkan Variasi Kondisi Ruangan (Studi Kasus Di Politeknik Terpikat Sambas) - Syahrizal, Iman; Panjaitan, Seno; ., Yandri (ELKHA : Jurnal Teknik Elektro, 2013)
Abstract The Objective of this research was to analyze effect of additionheat to electrical comsumption onAir Conditioner(AC). This research using a unit of split AC with capacity 9000 Btu/h and R22 refrigerant, set up on 4 x 4 meter room size. Condition of room experiment was varied by getting additionof heat from workers, electrical equipment and give some ventilation effect by opening the door every and 1 hour. The result of research showedthat by additionof cooling load in the room causing time required for conditioning thetestroomat 25 of temperature is longer, thus theelectrical energy consumed wasgreater. In theempty room, the timefor conditioning the test room at temperature up to 25oC is 1 hours, with electrical energyconsumptionis 1.26kWh. The roomwith3 people workers, 1computer and1Laptop, the time required is2hours with electrical energy consumptionis 1.68kWh. The roomwith3 people workers, 1 computer, 1 laptop and the door was opened with 50% wide everyhour, the time required is3hours with electrical energyconsumptionis 2.54kWh. The roomwith3 people workers, 1 computer, 1 laptopandthe door was opened with 50% wide every1hour, the time required is2hours with electrical energyconsumption is2.10kWh. Keywords Air Conditioner (AC), cooling load, electrical energy